Effects of Noninvasive Brain Stimulation Combined With Antidepressants in Patients With Poststroke Depression: A Systematic Review and Meta-Analysis - Liang, Jiabin; Feng, Jie; He, Jinhua; Jiang, Yong; Zhang, Haoyu; Chen, Hanwei (Frontiers in Pharmacology, 2022)
Objective: To evaluated the efficacy and safety of noninvasive brain stimulation (NIBS) combined with antidepressants in patients with poststroke depression (PSD). Methods: Seven databases were searched to identify randomized controlled trials of NIBS combined with antidepressants in the treatment of PSD based on the international classification of diseases (ICD-10) criteria and exclusion criteria. The retrieval time was from the database establishment to 31 October 2021. Two researchers independently screened the identified studies through the search strategy, extracted their characteristics, and evaluated the quality of the included literature. Cochrane Collaboration’s tool was used to assess risk of bias. RevMan 5.3 software was applied for meta-analysis. Results: A total of 34 randomized controlled trials were included, involving 2,711 patients with PSD. Meta-analysis showed that the total effective rate was higher in the combined therapy than the antidepressant alone [odds ratio (OR): 4.33; 95% confidence interval (CI): 3.07 to 6.11; p < 0.00001]. The Hamilton depressive scale (HAMD) score was significantly lower in repeated transcranial magnetic stimulation (rTMS) (≤10 Hz) combined with antidepressant than in antidepressant alone [standard mean difference (SMD): −1.44; 95% CI: −1.86 to −1.03; p < 0.00001]. No significant difference was seen in rTMS (>10 Hz) combined with antidepressant versus antidepressant alone (SMD: −4.02; 95% CI: −10.43 to 2.39; p = 0.22). In addition, combination therapy more strongly improved the modified Barthel index (MBI) scale than antidepressants [mean difference (MD): 8.29; 95% CI: 5.23–11.35; p < 0.00001]. Adverse effects were not significantly different between two therapies (OR: 1.33; 95% CI: 0.87 to 2.04; p = 0.18). Conclusion: Low-frequency rTMS (≤10 Hz) combined with antidepressants tends to be more effective than antidepressants alone in patients with PSD, and there are no significant adverse effects. In addition, combined therapy may enhance quality of life after stroke. Combination therapy with high-frequency rTMS (>10 Hz) showed no advantage in treating PSD. The transcranial electrical stimulation (TES) combined with antidepressants might be more effective than antidepressants alone, which are needed to confirm by more clinical trials since the.